Debit Analysis of Flood InPesayan Bridge Berau District - RACHMADIAN, AUDI (KURVA S JURNAL MAHASISWA, 2016)
AUDI RACHMADIAN, NPM: 12.11.1001.7311.284, Debit Analysis of Flood InPesayan Bridge Berau District, Supervisor: Dr. Ir. SRI yayuk SUNDARI, MT, and Supervisor II: HERI PURNOMO, ST, MT. Pesayanbridge in Berau is a means of liaison between JalanTalisayan from Berau to Makajang direction and vice versa. This bridge is separated by the river. To connect the road segments planned for the bridge. Planning bridge can not be done haphazardly, needs to be examined in detail and carefully so that the bridge has a long durability, ability to withstand the weight of the vehicle by which the and the resilience to natural events such as the rapid flow of river water during floods underneath return period.The purpose of this study was to determine the flood Debit Analysis on Bridge PesayanBerau DistrictFrom the analysis of the flood discharge at the river bridge PesayanBerau district, the maximum flood discharge method Nakayashu taken HSS return period of 100 years with the flood discharge (Q100) is the largest 952.58123282 m3 / sec.High elevation bridge from the bottom to the water surface taken by debit highest return period of 100 years (Q100) = 952.58123282 m3 / sec obtained water level (h) = 9,15 meters. Planning for a free high Pesayan River Bridge, District Sambaliung, Berau is planned minimal height is h + surveillance minimal = 2.00 + 9.15 = 11.15 meters. From the analysis of the flood water level coupled with the minimal surveillance height for the placement of the base Pesayan River bridge River Bridge to as high as 11.15 meters